2016
DOI: 10.1007/s00726-016-2195-2
|View full text |Cite
|
Sign up to set email alerts
|

Histidine and other amino acids in blood and urine after administration of Bretschneider solution (HTK) for cardioplegic arrest in patients: effects on N-metabolism

Abstract: Bretschneider (histidine-tryptophan-ketoglutarate, HTK) solution employed for induction of cardioplegic arrest possesses a high histidine concentration (198 mM). Due to the large volume administered, massive amounts of histidine are incorporated. The aim of the study was to evaluate alterations in amino acid and nitrogen metabolism originating from histidine degradation. Between 07/2014 and 10/2014, a total of 29 consecutive patients scheduled for elective isolated coronary artery bypass grafting with cardiopu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 31 publications
1
16
0
1
Order By: Relevance
“…Third, several studies have shown that HIS administration may lead to marked alterations in aminoacidaemia, which may impair signs of hepatic encephalopathy. Increases in glutamate, alanine, and glutamine concentrations and decreases in glycine and branched-chain amino acid (BCAA; valine, leucine, and isoleucine) concentrations in blood plasma have been reported frequently [39,59,[140][141][142][143].…”
Section: Side Effects Of Increased His Intakementioning
confidence: 99%
“…Third, several studies have shown that HIS administration may lead to marked alterations in aminoacidaemia, which may impair signs of hepatic encephalopathy. Increases in glutamate, alanine, and glutamine concentrations and decreases in glycine and branched-chain amino acid (BCAA; valine, leucine, and isoleucine) concentrations in blood plasma have been reported frequently [39,59,[140][141][142][143].…”
Section: Side Effects Of Increased His Intakementioning
confidence: 99%
“…In an experimental rat model of ex vivo lung perfusion, it was found that HTK solution attenuated pulmonary edema until 12 h post-perfusion compared to both saline and low-potassium dextran solution, another extracellular based preservation solution [ 42 , 43 ]. We have recently shown that lung ischemia-reperfusion injury during CPB is characterized by augmented inflammation, metabolic acidosis, protease activity, and oxidative stress and that patients receiving lung protection with HTK solution seemed better protected against severe acidosis, excessive fatty acid oxidation, and inflammation compared to pulmonary artery perfusion with normothermic oxygenated blood or no pulmonary perfusion during CPB [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the operation as well as in the postoperative phase, patients received different fluids intravenously (Table 1), according to those values published previously [4, 16]. …”
Section: Methodsmentioning
confidence: 99%